Public social security burden of musculoskeletal diseases in Brasil-Descriptive study - Passalini,Thaysa Simões Paixão (2018)
SUMMARY BACKGROUND: To present data on the social security burden of diseases of the musculoskeletal system and connective tissue (DSOTC) in Brasil in 2014, and evolution of these social security expenditures between 2009 and 2014. METHOD: Compilation and analysis of data on the granting of disability pensions and sickness benefits in the year 2014, available on the official website of Social Security, classified according to ICD 10. It was evaluated the evolution between 2009 and 2014, using the F test to compare the curves with the growth of the active age population (PIA). RESULTS: Among the 22 disease groups classified according to ICD-10, the DSOTC group led benefits grants in 2014, with 19% of the sickness benefits and 13.5% of the disability pensions. The main causes of sickness benefit and disability retirement were, respectively: dorsopathies (43.3% and 41.2%), soft tissue diseases (27.3% and 19.7%), osteoarthritis (7.6% % And 27.8%) and chronic inflammatory arthropathies (2.8% and 7.9%). In the evolution of the number of sickness benefits granted between 2009 and 2014, both INSS and DSOTC totals showed an increasing tendency (35.9 and 35.3%, respectively, with p = 0.000 for both). As for disability retirement, there was a 5.9% increase in the INSS total (p = 0.039), while for the DSOTC there was a decrease of 7.6% (p = 0.005). CONCLUSIONS: These data point to a progressive increase in the granting of sickness pensions and disability benefits in the country, superior to the growth of the PIA, as well as a high participation of DSOTC in these benefits.